A method for evaluating the results of tendon transfers for foot drop - Yeap, Joo Seng; Singh, Dishan; Birch, Rolfe (Lippincott, Williams & Wilkins, 2001)
A system for assessing the results of tibialis posterior tendon transfers in the treatment of foot drop secondary to nerve palsy is proposed. There are seven sections to this scoring system: pain, need for orthosis, ability to wear normal shoes, activity level, muscle power of ankle dorsiflexion, degree of active ankle dorsiflexion, and foot posture. The total score is 100. The results are classified as excellent for scores between 85 and 100, good between 70 and 84, fair between 55 and 69, and poor for scores below 55. The results of 18 patients (mean followup, 64.6 months) who had a tibialis posterior tendon transfer were assessed using this method. Four patients (22.2%) had an excellent result, seven (38.8%) had a good result, two (11.1%) had a fair result, and five (27.7%) had a poor result. The average score was 67.2, suggesting an overall fair result for this operation. In nine patients, there was correlation between the outcome when assessed with this method and with patient rating. In two patients, the outcomes were better when assessed with this method than with patient rating, whereas the reverse was true in seven other patients. Thus, this system may provide a more objective and critical evaluation of tibialis posterior transfers for foot drop.